EFFECTIVENESS OF LIFESTYLE MODIFICATION ON WEIGHTLOSS AND QUALITY OF LIFE IN OBESE WOMEN WITH POLYCYSTIC OVARIAN SYNDROME - Patil, Vinaya Rajendra; Thangavelu, Poovishnu Devi; Jagtap, Vaishali Krishnat (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: (1) The objectives of this study were to determine the effectiveness of lifestyle modification on weight loss and the quality of life in obese women with the polycystic ovarian syndrome and (2) to determine the effectiveness of conventional physiotherapy on weight loss and the quality of life in obese women with polycystic ovarian syndrome. Methods: Ethical clearance was obtained from the Institutional Ethical Committee. A total of 40 obese women with the polycystic ovarian syndrome (PCOS) were selected and divided into two groups, Group A (N=17) received conventional physiotherapy alone, and Group B (n=15) received lifestyle modification along with conventional physiotherapy. The preassessment of body weight is measured by body mass index (BMI); the waist-hip ratio (W-H ratio) and body fat percentage and the quality of life were scored as per the PCOS questionnaire (PCOSQ); and postinterventional assessment was taken for the same after 9 months. Result: Intergroup statistical analysis for BMI revealed extremely significant in postintervention for Group B (P<0.0001). W-H ratio and PCOSQ were extremely significant for Group B (P<0.0001). While postintervention analysis showed extremely significant difference between Group A and Group B (P<0.0001). Group B treated with lifestyle modification, and conventional physiotherapy was extremely significant. Conclusion: Lifestyle modification with conventional physiotherapy helped in reducing weight and showed the increased quality of life in women with PCOS.